Small and Large Firm Performance Gaps in Indonesia: Evidences from the 1981–2008 Indonesian Manufacturing - Ari Kuncoro (Jurnal Ekonomi Indonesia, 2019)
This study aims to examine the impacts of globalization on the performance gap between small and large firms in Indonesia, specifically in the manufacturing sector. First, the study addresses whether there are performance differentials between small and large firms, and if so, whether such gap is increasing while controlling for firm characteristics such as age, finance, export orientation, industry, and macroeconomic indicators. Second, the study discusses whether the opening of domestic market through trade and FDI liberalization affect firms disproportionately with respect to firm size. The study highlights such impacts amid successive economic reforms from 1986 to 1994. The empirical results suggest that opening the economy through market liberalization increased the productivity and wages gaps between large and small firms before it stabilized. Factors such as industrial agglomeration, financial access, export orientation have minimal impact on firms. The findings also suggest that while empirically, small firms benefit from more open trade regime after Asian financial crisis, the medium and large firms have more chance to benefit from the liberalization of the economy in general. Policy implications are also further explored.